2015
DOI: 10.1039/c5ra00804b
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activities of TiO2nanotubes on Porphyromonas gingivalis

Abstract: The potential impacts of TiO2 nanotubes on Porphyromonas gingivalis growth and drug resistance were investigated. TiO2 nanotubes antibacterial performance can be manipulated with the photocatalytic activity as well as the geometry characteristic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Nano-topography and surface energy were affected by the coating structure: interestingly, at a sub-micro scale, both the crystalline oxides surfaces exhibited higher numbers of attached bacteria. In addition, in a recent study [85], the antibacterial effects of TiO 2 nanotubes could be attributed to the oxidative stress induced as well as geometrical characteristics. Table 1 provides a synthetic reference on the different types of biological effects that have been reviewed in this section, with proper references.…”
Section: Nanostructured Surface Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nano-topography and surface energy were affected by the coating structure: interestingly, at a sub-micro scale, both the crystalline oxides surfaces exhibited higher numbers of attached bacteria. In addition, in a recent study [85], the antibacterial effects of TiO 2 nanotubes could be attributed to the oxidative stress induced as well as geometrical characteristics. Table 1 provides a synthetic reference on the different types of biological effects that have been reviewed in this section, with proper references.…”
Section: Nanostructured Surface Modificationsmentioning
confidence: 99%
“…Titania nanotubes engineered by electrochemical anodization process have been proposed to develop drug-releasing implants in orthopedics and dentistry [83][84][85] owing to their biocompatibility (for a complete review, please refer to [83]). As the prolongation of drug release from these nano-reservoirs is still a challenge, the relation between nanotube dimensions (diameter, length, aspect ratio and volume) and drug release rate was investigated finding that systems with higher aspect ratios released drug slower [84].…”
Section: Antimicrobial Featuresmentioning
confidence: 99%
“…It has recently been shown that a titanium nanotube surface exhibited antimicrobial properties and down-regulated the glycosyltransferase genes of S. mutans 171) . All studies that tested surfaces with a combination of nanostructures and organic or inorganic antimicrobial chemical compounds on the nano-level found reduced bacterial adhesion and viability 31,34,43,[59][60][61][62]97,135,137) . Surfaces containing Ag NPs show excellent biocidal activity towards P. aeruginosa, S. oralis, S. mutans, P. gingivalis, S. aureus 143,144) , S.…”
Section: Nanoscale Surfacesmentioning
confidence: 99%
“…Increased hydrophilicity results in increased antibacterial performance due to higher surface energy, as has been demonstrated by an increasing number of studies. 19,38,39 As shown in Table 1 and Figures 3 and 4, compared with TNT, the surface roughness of the TiAg-NT samples increased slowly with an increase in the Ag content, and the differences among the samples were insignificant (P.0.05). As shown in Figure 5, the TiAg-NT samples were less hydrophilic than TNT, and decreased hydrophilicity was obtained with an increase in the Ag content.…”
mentioning
confidence: 97%
“…The surface roughness was tested by confocal laser scanning microscopy (LEXT OLS4100, Olympus Corporation, Tokyo, Japan), and the water contact angle of each sample at room temperature was measured using image collection and analysis systems (DataPhysics OCA20; DataPhysics Instruments GmbH, Stuttgart, Germany) with distilled water as the determining medium. 19 …”
Section: Surface Characterizationmentioning
confidence: 99%